Opioid Rotation vs. Dose Titration in Refractory Cancer Pain: A Meta-Analysis of Efficacy and Adverse Events - Arina Widya Murni; Dian Arfan As Bahri; Widya Deli Satuti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The management of refractory cancer pain represents a formidable clinical challenge at the intersection of oncology and palliative medicine. When patients with advanced malignancy fail to achieve adequate analgesia or develop intolerable adverse effects from their opioid regimen, clinicians are faced with a crucial decision: to escalate the dose of the current opioid (dose titration) or to switch to a different opioid agent (opioid rotation). The optimal strategy remains a subject of intense debate and variable practice. This meta-analysis was conducted to rigorously compare the efficacy and safety of these two common interventions. Methods: A systematic and comprehensive search was performed in the PubMed, EMBASE, and Cochrane Central Register of Controlled Trials databases for randomized controlled trials (RCTs) published between January 2015 and December 2024. We included studies that directly compared opioid rotation with dose titration in adult palliative care patients diagnosed with refractory cancer pain. The primary efficacy outcome was the change in pain intensity, analyzed using the Standardized Mean Difference (SMD) to accommodate pain scales such as the Numerical Rating Scale (NRS) and Visual Analogue Scale (VAS). Primary safety outcomes were the incidence of severe neurotoxicity and severe constipation. Data were pooled using a random-effects model, and results were expressed as SMD for the continuous pain outcome and Risk Ratio (RR) for dichotomous adverse events, with corresponding 95% confidence intervals (CI). Results: Seven RCTs, encompassing a total of 962 patients, met the stringent inclusion criteria. The pooled analysis revealed that the strategy of opioid rotation resulted in a statistically significant and clinically substantial greater reduction in pain intensity compared to continued dose titration (SMD -0.65, 95% CI [-0.88, -0.42], p<0.00001; I²=81%). Furthermore, the risk of developing severe neurotoxicity, including delirium and myoclonus, was significantly lower in the rotation group (RR 0.62, 95% CI [0.45, 0.85], p=0.003; I²=18%). There was no statistically significant difference in the incidence of severe constipation between the two intervention groups (RR 0.90, 95% CI [0.71, 1.14], p=0.38; I²=24%). Conclusion: In patients with refractory cancer pain, the strategy of opioid rotation provided superior analgesia and was associated with a markedly lower risk of severe neurotoxicity when compared to the continued dose titration of the same opioid. These findings provide strong, high-level evidence to support the use of opioid rotation as a primary and proactive strategy for managing uncontrolled pain or dose-limiting side effects in the palliative care population.